Exploiting investor sentiment for portfolio optimization - Nicolas Banholzer; Sebastian Heiden; Dominik Schneller (Business Research, 2019)
The information contained in investor sentiment has up to now hardly been used for portfolio optimization, although theoretical works demonstrate that it should not be neglected and it has already been shown to contain exploitable information on future returns and volatility. Employing the approach of Copula Opinion Pooling, we explore how sentiment information regarding international stock markets can be directly incorporated into the portfolio optimization procedure. We subsequently show that sentiment information can be exploited by a trading strategy that takes into account a medium-term reversal effect of sentiment on returns. This sentiment-based strategy outperforms several benchmark strategies in terms of different performance and downside risk measures. More importantly, the results remain robust to changes in the parameter specification.
Keywords: G11; G15; G17; 650; Portfolio optimization; Investor sentiment; Copula opinion pooling; Behavioral finance